2009
DOI: 10.1007/s10499-009-9249-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of culture density and bottom area on growth and survival of the cuttlefish Sepia officinalis (Linnaeus, 1758)

Abstract: The effects of culture density and bottom areas on cuttlefish (Sepia officinalis) culture were studied. Cuttle fish were cultured under three experimental combinations of culture density and bottom area: (1) high density and small bottom surface area; (2) low density and large bottom area; (3) high density and large bottom area. Each experimental protocol was repeated in triplicate. Average weights at the end of the experiment were of 65.8 ± 5.8, 87.1 ± 5.6 and 78.7 ± 5.9 g for cuttlefish cultured under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
8
1
2
Order By: Relevance
“…reported growth rates *1% body weight day -1 at culture densities ranging between 4 and 25 kg m -3 . Similar results were reported for O. vulgaris (Segawa and Hanlon 1988;Iglesias et al 2000;Aguado and García-García 2003) and Sepia officinalis (Domingues and Márquez 2010).…”
Section: Introductionsupporting
confidence: 86%
“…reported growth rates *1% body weight day -1 at culture densities ranging between 4 and 25 kg m -3 . Similar results were reported for O. vulgaris (Segawa and Hanlon 1988;Iglesias et al 2000;Aguado and García-García 2003) and Sepia officinalis (Domingues and Márquez 2010).…”
Section: Introductionsupporting
confidence: 86%
“…On the other hand, Domingues and Marquez () observed an overall increase in growth and survival rates associated with increased bottom areas regardless of rearing densities. Nevertheless, these authors used raceway tanks contrary to the circular tanks used by Correia et al .…”
Section: Discussionmentioning
confidence: 96%
“…According to Sykes, Domingues & Andrade (), Forsythe, Lee, Walsh and Clark () and Correia, Domingues, Sykes and Andrade (), available bottom areas, animal density and temperature interfere with cuttlefish growth, mortality and reproduction. Recently, Domingues and Marquez (), concluded that larger bottom areas of raceway tanks have significant effects on cuttlefish growth and survival at different densities. This may be due to the ability of the species for spatial learning, which was previously described by Karson, Boal and Hanlon ().…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los factores clave en la acuicultura es optimizar el crecimiento en un mínimo de espacio (Forsythe et al 2002, Iglesias et al 2002, Domingues et al 2003 evitando una excesiva masificación de individuos, que puede tener efectos negativos sobre el crecimiento y el comportamiento de muchas especies. La densidad de cultivo es pues un factor muy importante en acuicultura (Sumpter 1993).…”
Section: Introductionunclassified